2017
DOI: 10.3389/fnhum.2017.00273
|View full text |Cite
|
Sign up to set email alerts
|

Music Games: Potential Application and Considerations for Rhythmic Training

Abstract: Rhythmic skills are natural and widespread in the general population. The majority can track the beat of music and move along with it. These abilities are meaningful from a cognitive standpoint given their tight links with prominent motor and cognitive functions such as language and memory. When rhythmic skills are challenged by brain damage or neurodevelopmental disorders, remediation strategies based on rhythm can be considered. For example, rhythmic training can be used to improve motor performance (e.g., g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 73 publications
0
28
0
3
Order By: Relevance
“…The safety and effectiveness of several commercial exercise gaming (exergaming) systems for motor rehabilitation in PD patients have been extensively investigated [15][16][17][18][19][20][21]. Two prospective studies reported that exercises using the virtual-reality-based Wii Fit substantially improved obstacle-crossing performance, dynamic balance, and attention in patients with mild-to-moderate PD (HY stage 3 or lower) [19,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The safety and effectiveness of several commercial exercise gaming (exergaming) systems for motor rehabilitation in PD patients have been extensively investigated [15][16][17][18][19][20][21]. Two prospective studies reported that exercises using the virtual-reality-based Wii Fit substantially improved obstacle-crossing performance, dynamic balance, and attention in patients with mild-to-moderate PD (HY stage 3 or lower) [19,21].…”
Section: Introductionmentioning
confidence: 99%
“…A recent short review found that most of the commercially available rhythm-based games were insufficient for training rhythmic skills, although some features of the games were interesting. Hence, this review concluded that current rhythm-based games still required further modification to devise efficient rhythmic training programs for patients with motor or cognitive impairment [ 15 ]. A systematic review published in 2014 concluded that commercial exergames (Nintendo Wii Fit platform and Sony Playstation Eye) often require fast and complex responses that may be too difficult for some PD patients; therefore, specifically tailored exergames are needed to meet the safety and rehabilitation needs of patients with mild-to-moderate PD [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…From the above results, it was found that playing a rhythm game increases the processing speed for complicated tasks, and this study also found that the degree of selective attention increased during the rhythm game. Bégel et al (2017) conducted systematic reviews about music games to verify the beneficial effects of rhythm training and found that training using rhythm games has a positive effect on cognitive function and human movement. In addition, they mentioned that rhythm games might be adopted to cognitive training.…”
Section: S500mentioning
confidence: 99%
“…(ppy pty Ltd., Australia) is a free online rhythm game that a player taps a series of circles to the beat of the music, occasionally dragging a ball or rotating a spinner on the screen as well. Bégel et al (2017) conducted a review study to verify the beneficial effects of rhythm games, and study mentioned that training using rhythm games has a positive effect on cognitive function and physical rhythm perception. However, there is no scientific evidence has not been validated and needs to be validated for use by eSports athletes as a training tool.…”
Section: Introductionmentioning
confidence: 99%
“…Also, it is reported that gamers of this genre have shown high level rhythm recognition skills on certain musical instrument through playing [5,6]. The educational effect of this genre, however, is not clearly shown by a systematic review [7] but its intrinsic value on potential creativity learning is encouraged [8,9].…”
Section: Introductionmentioning
confidence: 99%